Micropropagation of Kratom (Mitragyna speciosa (Korth.) Havil.): Disinfectants, Growth Regulators, and Low-Cost Chemical Disinfection for In Vitro Establishment - Sookruksawong, Suchonma (Asian Health, Science and Technology Reports, 2024)
Kratom, Mitragyna speciosa (Korth.) Havil. is a medicinal plant native to Southeast Asia that is renowned for its therapeutic properties and potential in treating various ailments. Despite its significance, the cultivation and propagation of Kratom have been limited. The purpose of the present study was to develop a cost-effective micropropagation protocol for Kratom by investigating the disinfection efficiency and cost-effectiveness of various chemical disinfectants, optimizing plant growth regulator concentrations, and assessing cost-effective media sterilization methods. The results demonstrated that double disinfection with commercial bleach at 20% and 15% for 5 min each was the most cost-effective treatment for surface disinfection of Kratom seeds, achieving a high disinfection rate (96.67±2.89%) and survival rate (73.33±2.89%) at a relatively low cost (1.46 baht per experiment) compared to mercuric chloride (HgCl2) treatments. The evaluation of benzyladenine (BA) and naphthaleneacetic acid (NAA) effects on in vitro growth revealed that the control treatment (MS (Murashige and Skoog medium) without growth regulators) exhibited the best overall growth performance. Among the low-cost disinfectants tested for the culture medium, while autoclaving offers superior disinfection efficacy, commercial bleach at 2 ml/l emerged as the most cost-effective option, especially for resource-limited operations. The final choice, however, should align with specific operational requirements, including scale, resources, and the need for complete disinfection. The successful establishment of a cost-effective micropropagation protocol using low-cost chemical disinfectants and optimized plant growth regulator concentrations can significantly reduce the production costs associated with tissue culture techniques, making the micropropagation of Kratom more economically viable and accessible for large-scale production. The findings from this research provide insights into cost-effective micropropagation methods for Kratom, which will prove valuable for future studies and applications in the field.